The Future of Sustainability Reporting: How ESG Metrics Are Reshaping Corporate Valuation and Investment Strategies Across Global Markets - Mbonigaba Celestin; Mishra, Anjay Kumar (Journal of Advanced Research in Operational and Marketing Management, 2025)
Purpose This study examines the evolving role of Environmental, Social, and Governance (ESG) reporting in corporate valuation from 2020 to 2024, focusing on its impact on financial performance, investor behavior, and consumer trust. Design/Methodology/Approach A mixed-method approach was employed, combining regression analysis, correlation studies, and machine learning-based sentiment assessments. The sample included 250 publicly traded firms across major industries, with data analyzed to quantify ESG transparency’s influence on market performance and stakeholder perceptions. Findings Financial Performance: A strong positive correlation exists between ESG transparency and stock market performance (r = 0.995, p< 0.001). ESG-focused firms outperformed traditional investments, delivering an average annual return of 22% versus 10%. Profit Margins: Regression analysis revealed that every 100 billion invested in ESG initiatives increased profit margins by 2 percentage points (R² = 1.000, p< 0.001). Consumer Trust: High ESG-compliant firms achieved 85% consumer trust, compared to 50% for low ESG performers. Challenges: Persistent issues include standardization gaps, data reliability concerns, and the need for AI-driven verification mechanisms. Originality/Value This study pioneers the integration of machine learning for sentiment analysis in ESG contexts and provides empirical evidence linking ESG transparency to quantifiable financial gains. It advances the discourse on ESG-driven governance by proposing novel frameworks for embedding sustainability into core financial reporting. Practical Implications Regulatory Action: Mandate third-party ESG audits and harmonize global reporting standards to enhance comparability. Corporate Strategy: Incentivize sustainability through tax benefits and reduced financing costs for high-ESG firms. Investor Guidance: Develop AI-powered tools to verify ESG claims, mitigating greenwashing risks and improving decision-making. Conclusion The findings underscore sustainability as a critical determinant of long-term financial success, urging stakeholders to prioritize ESG integration in valuation models and governance frameworks.